Midday Meal Consumption Practice Among Basic School Children: A Cross-Sectional Study in Kathmandu - Rai, Devi Kala; Upreti, Yadu Ram; Pokhrel, Mahesh; Acharya , Devaraj (Journal of Health Promotion, 2024)
The present study aimed to examine the midday meal (MDM) consumption practice among the upper-basic level school children from grades 6–8. A cross-sectional quantitative study was conducted among 323 students selected from two community schools in Budhanilkantha Municipality, Kathmandu. Data were collected using a self-administered questionnaire consisting of closed-ended items. Data were collected face-to-face in students’ classrooms after obtaining permission from the school authorities and obtaining written consent and assent from students and parents. The data were analysed using SPSS version 25, applying descriptive analysis such as frequency percentages, central tendency, and measure of dispersion, as well as bivariate analysis such as the chi-square test. The findings of the study revealed that though more than three-fourths (78.2%) of the students consumed MDM regularly, nearly two-thirds (60%) of them consumed junk food as part of their MDM at school. The results also demonstrated that students’ socio-demographic factors such as sex, grade, and father’s occupation are significantly associated with MDM consumption practices. The results of the study underscore the need to extend the MDM program to upper-basic schools and implement school-based health intervention(s) aimed at fostering healthy dietary behaviors among basic school children in their formative stage of life.